Effect of heparanase inhibitor on tissue factor overexpression in platelets and endothelial cells induced by anti‐β2‐GPI antibodies. (4th July 2021) - Capozzi, Antonella; Riitano, Gloria; Recalchi, Serena; Manganelli, Valeria; Costi, Roberta; Saccoliti, Francesco; Pulcinelli, Fabio; Garofalo, Tina; Misasi, Roberta; Longo, Agostina; Di Santo, Roberto; Sorice, Maurizio
Abstract: Background: Anti‐phospholipid syndrome (APS) is characterized by arterial and/or venous thrombosis and pregnancy morbidity associated with the presence of "anti‐phospholipid antibodies." Thrombosis may be the result of a hypercoagulable state related to activation of endothelial cells and platelets by anti‐β2‐glycoprotein I (β2‐GPI) antibodies. Anti‐β2‐GPI antibodies induce a proinflammatory and procoagulant phenotype in these cells that, after activation, express tissue factor (TF), the major initiator of the clotting cascade, playing a role in thrombotic manifestations. Moreover, TF expression may also be induced by heparanase, an endo‐β‐D‐glucuronidase, that generates heparan sulfate fragments, regulating inflammatory responses. Objectives: In this study we analyzed, in human platelets and endothelial cells, the effect of a new symmetrical 2‐aminophenyl‐benzazolyl‐5‐acetate derivative (RDS3337), able to inhibit heparanase activity, on signal transduction pathways leading to TF expression triggered by anti‐β2‐GPI. Methods: Platelets and endothelial cells were incubated with affinity purified anti‐β2‐GPI after pretreatment with RDS3337. Cell lysates were analyzed for phospho‐interleukin‐1 receptor‐associated kinase 1 (IRAK1), phospho‐p65 nuclear factor kappa B (NF‐κB) and TF by western blot. In addition, platelet activation and secretion by ATP release dosage were evaluated. Results: IRAK phosphorylation and consequent NF‐κB activation, as well as TF expression triggered by anti‐β2‐GPI treatment were significantly prevented by previous pretreatment with RDS3337. In the same vein, pretreatment with RDS3337 prevented platelet aggregation and ATP release triggered by anti‐β2‐GPI antibodies. Conclusion: These findings support the view of heparanase involvement in a prothrombotic state related to APS syndrome, suggesting a novel target to regulate overexpression of procoagulant protein(s).